ANALISIS DAN EVALUASI STRATEGI BERSAING DALAM UPAYA PENINGKATAN VOLUME PENJUALAN SEPEDA MOTOR HONDA DI WILAYAHSUMATERA UTARA (STUDI KASUS: MAIN DEALER SEPEDA MOTOR HONDAWILAYAH SUMATERA UTARA CV. INDAKO TRADING CO. JL. PEMUDA NO. 18 DEFGH, MEDAN) - JefrY Sudono Halim; Rismayani .; Sutarman . (Al-Irsyad: Jurnal Pendidikan dan Konseling, 2015)
Strategies are being made to increase the volume of sales of Honda motorcyclesin 2013 of raising consumer awardness to Honda through an ad campaign. Viewed fromthe strategy that has been implemented in 2013, the sales unit has not reached thepredetermined targets, but seen from the market share has increased (seize the marketshare of competitors). Realized sales from the year 2009-2011 increased volume salesof Honda motorcycles, while from 2011- 2013 year decline in sales volume Hondamotorcycles. The purpose of this study was to determine the effect of variable brands,design, features, quality, price, sale, resale value, and after-sales service to variableinterest of consumers simultaneously and partially and competitive strategy that iseffective to increase the volume of sales of the Honda Motorcycle in North Sumatra.Keywords: Minat Konsumen, Strategi Bersaing, Volume Penjualan.